2020
DOI: 10.1002/star.201900303
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Changes and In Vitro Digestibility of Maize Starch Treated with Different Calcium Compounds Used in Nixtamalization Processes

Abstract: Maize starch dispersions (5 g/100 mL water) are treated with Ca(OH)2 (0.2 g/100 g starch), emulating the traditional nixtamalization process, and with CaCl2 or Ca(CO)3 (1.0g/100 g starch) salts, emulating ecological nixtamalization processes. The effect of these calcium compounds upon the in vitro digestibility of maize starch is evaluated in comparison to an untreated starch dispersion used as control. The Ca(OH)2 treatment significantly increases the rapidly digestible starch (RDS) fraction (from ≈33 to 64%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…[ 33,34 ] The shifting to distant positions may be reflecting the formation of calcium‐mediated ordered structures. [ 35 ] Table 3 also presents the intensity ratios R h / a and R o / a for the xerogel variations. The magnitude of both ratios increased with the starch content.…”
Section: Resultsmentioning
confidence: 99%
“…[ 33,34 ] The shifting to distant positions may be reflecting the formation of calcium‐mediated ordered structures. [ 35 ] Table 3 also presents the intensity ratios R h / a and R o / a for the xerogel variations. The magnitude of both ratios increased with the starch content.…”
Section: Resultsmentioning
confidence: 99%
“…Calcium carbonate and Ca chloride have also been used as nixtamalization agents, and experiments conducted on maize plants showed that treatment with these agents could lead to modifications in the digestibility of resistant and soluble starches (Roldan-Cruz et al, 2020). Cooking reduces the oxalate content of the food by discharging losses into the cooking water (Savage et al, 2000).…”
Section: The Effect Of Processing and Cooking Procedures On The Calcium Contentmentioning
confidence: 99%
“…(2020) 60 asegura que brinda mayor viscosidad debido a que, de acuerdo a estudios de digestión in vitro, contiene mayor almidón de lenta digestión, así como más almidón resistente, en comparación con el tratamiento tradicional, lo cual beneficia la cantidad de fibra de la tortilla.…”
Section: Modificación De Los Componentes Del Maíz Durante La Nixtamalizaciónunclassified